Mycosphaerella and other fungi associated with banana leaf diseases from Northern Thailand - Kaewjan,P. (Chiang Mai University, 2015)
The Mycosphaerella species associated with banana leaf disease were initially identified by integrating the morphological characteristics and analysis of DNA sequence data; four taxa including Mycosphaerella eumusae, M. musae, Cercospora hayi and Pseudocercospora callicarpae were revealed. Mycosphaerella eumusae has previously been reported on banana from Thailand, whereas M. musae, C. hayi and Ps. callicarpae are new records. Cordana musae and Deightoniella torulosa were also frequently isolated from diseased banana leaf tissues. Other less common taxa include Alternatia, Colletotrichum, Curvularia, Fusarium, Periconia and Periconiella species. The effectiveness of chemical control of eumusae leaf spot of banana was determined over one month to establish the effectiveness of different chemical fungicides. Among all the treatments, rotational spraying with difenoconazole and mancozeb at weekly intervals gave the most effective and economical control.